Music Interventions for Neurodevelopmental Disorders - Antonietti, Alessandro (Springer International Publishing, 2018)
This book explores how music can improve skills that are impaired in some neurodevelopmental disorders, including ADHD (attention deficit hyperactivity disorder), autism, and Rett syndrome. Rehabilitation interventions based on the use of music, termed "music therapy", are relatively widespread, but not all are supported by empirical evidence. This book offers readers an updated and scientifically grounded perspective on this theory and argues that music can be effective in promoting the acquisition of some basic mental abilities. Chapters present some of the latest research and data on how musical activities can lead children affected by neurodevelopmental disorders to improve those skills, including examples of training programs and exercises. The book will be a valuable resource for therapists, rehabilitators, psychologists, educators, musicians, researchers, as well as anyone interested in exploring the potential in music for human growth. Alessandro Antonietti is Professor of Applied Cognitive Psychology at the Catholic University of the Sacred Heart, Italy. There he is the head of the Department of Psychology and coordinates the Cognitive Psychology Lab. His research interests lie in the applications of cognitive issues in the field of instruction and rehabilitation. Barbara Colombo is Associate Professor of Cognitive Neuroscience at Champlain College, USA, where she is Head of the Neuroscience Lab. Her most recent research has been focused on exploring the role of individual differences in modulating cognitive and emotional behaviours. Braelyn R. DeRocher is affiliated with the Neuroscience Lab at Champlain College, USA. His research interests are related to empathy, aggression, and personal empowerment, focusing on at-risk youth.